(untitled) (The International Journal for Scientific Research, 2023)
The STM studies of Fe films with thickness above 0.6 ML do not contribute significantly to the solution of the structural problems, because of the Au surface layer, which hinders details of the Fe sub-surface layers. The Mossbauer spectroscopy appears in this case as an exceptional method, which has the ability to solve structural and magnetic problems. Our discussion is based on a simplified spectrum analysis, assuming a discrete character of the spectral components. In reality, a distribution of the hyperfine magnetic field, as well as isomer shift and the quadrupole splitting is an obvious and natural consequence of the finite size system ’presented by the monolayer film. The exact fitting of all hyperfine parameters distribution is too difficult. Most of the fitting procedures treat the distributions of IS vs. Bhf and QS vs. Bhf as linearly dependent as described using the well-known Voigt-based method.